Current approaches to alternative therapy in menopausal syndrome (a review) - A. G. Mamontova; Е. N. Usoltseva (Акушерство, гинекология и репродукция)
Vasomotor symptoms are most common signs of the menopausal syndrome. Frequent episodes of flushes and hyperhidrosis affect sleep, mood, and quality of life. Menopausal hormone therapy (MHT) remains the «gold standard» of treatment. However, some women have contraindications to MHT, and others refuse to take hormones due to personal reasons. In such cases, alternative therapy may become an option. This article presents a review of the literature regarding the role of alternative therapy in the treatment of vasomotor symptoms. We searched Russian and international data bases for pharmacological products (natural and synthetic) used to relieve menopausal flushes. The review presents medication registered in the Russian Federation as well as products used abroad.